Tales from a not-so-happy birthday - Russell, Rachel Renée; Russell, Nikki; Russell, Erin (Russell, Rachel Renée. Dork diaries ;, 2018)
Nikki's best friends want to throw her a birthday party with cake, special invitations, and even a DJ. But when her mom claims the party is too expensive, Nikki thinks her birthday might be a bust.